The Effects of Perceived Freedom in Leisure on Leisure Benefits: Students of The Faculty of Sports Science - Emrah Serdar (Türk Spor ve Egzersiz Dergisi)
This study aims to determine the differences between the levels of perceived freedom in leisure and the leisure benefits in terms of specific socio-demographic characteristics of the students studying in the faculty of sports sciences, the predictive power of the levels of the perceived freedom in leisure on their leisure benefit levels. A total of 318 participants, including 199 male and 119 female, studying in different sports sciences faculties selected by the convenience sampling method, constitute the sample. In addition to the Personal Information Form, the “Perceived Freedom in Leisure Scale-25” developed by Witt and Ellis (34) and firstly adapted to Turkish by Lapa and Kaas (22) and the “Leisure Benefit Scale” developed by Ho (15) and adapted to Turkish by Akgül et al. (2) were used as data collecting tools in the study. Descriptive statistics, independent t-test, ANOVA, MANOVA, and regression analysis were adopted in the analysis of the data. The independent t-test results showed no significant difference between the levels of individuals' perceived leisure levels by their gender. The ANOVA results showed no difference between the participants' satisfaction status and the levels of perceived freedom in leisure per week. The MANOVA results showed that the effect of individuals’ gender, welfare status, and weekly leisure on their leisure benefit levels was not significant and that there were no statistical differences between the sub-dimensions. To the results of regression analysis, the perceived freedom in leisure is an important predictor of leisure benefit. Consequently, the research revealed that the levels of perceived freedom in leisure and leisure benefit do not differ based on socio-demographic characteristics and that the perceived freedom in leisure is an essential factor in participants' benefits.